Re-visiting laparoscopic radical nephrectomy- the past, present and future: case report and review of literature - Shetty, Saiprasad; Shetty, Prakash; Joshi, Abhijit (International Surgery Journal, 2021)
Laparoscopic radical nephrectomy (LRN) has since long proven its therapeautic credentials in the field of renal cancer. Since the first reported case of LRN thirty years ago, it has stood the test of time. With the development of newer energy sources, better optics and ergonomically superior instruments, it has further established itself as the milestone or the landmark with which all future variations in the field of renal cancer surgery would be compared. Newer procedures such as retroperitoneoscopic radical nephrectomy, laparoscopic partial nephrectomy, robotic radical nephrectomy and partial nephrectomy and few other more conservative procedures such as radio-frequency ablation, cryo-ablation etc. are examples of these variations. In this paper, we present a case report on laparoscopic radical nephrectomy, review literature on the subject and delve into comparisons with newer procedures vis-à-vis their individual pros and cons. Through this study we are portraying the past, present and future of laparoscopic radical nephrectomy.